The everyday architectural experience: A comparative study among threeprovinces of Thailand - Jumsai na Ayudhya, Thirayu (My University, 2018)
The study of what architecture means to people in their everyday lives inadequately addresses the contextualized and holistic theoretical framework. This article succinctly presents theoretical framework obtained from the comparative study of how people experience the everyday architecture in three different contexts including 1) Bangkok CBD, 2) Phuket island old-town, and 3) Nan province old-town. The way people make sense of the everyday architecture can be addressed in four super-ordinate themes; (1) building in urban (text), (2) building in (text), (3) building in human (text), (4) and building in time (text). In this article, these super-ordinate themes were verified whether they recur in three studied-contexts. In each studied-context, the participants were divided into two groups, 1) local people, 2) visitors. Participants were asked to take photographs of the everyday architecture during the everyday routine and to participate the elicit-interview with photographs produced by themselves. Interpretative phenomenological analysis (IPA) was adopted to interpret elicit-interview data. Sub-themes emerging in each studied-context was brought into the cross comparison among three studied- contexts. It is found that four superordinate themes recur with additional distinctive sub-themes. Further studies in other different contexts, such as socio-political, economic, cultural differences, are recommended to complete the theoretical framework.
Keywords: Architectural experience; Architecture; Architecture environment of pedestrian street; Architecture of public buildings; City; Space and place; The everyday architecture